Sozialistische Mitteilungen : . Sozialistische Mitteilungen der London-Vertretung der SPD
Since (1946):Oct. titled: Sozialistische Mitteilungen der London-Vertretung der SPD. - For suppl. see: Survey of the discussion on the future of Germany in daily papers and periodicals (ZO 6666).